2019
DOI: 10.1080/17435390.2019.1570372
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-378a as a key regulator of cardiovascular health following engineered nanomaterial inhalation exposure

Abstract: Nano-titanium dioxide (nano-TiO 2), though one of the most utilized and produced engineered nanomaterials (ENMs), diminishes cardiovascular function through dysregulation of metabolism and mitochondrial bioenergetics following inhalation exposure. The molecular mechanisms governing this cardiac dysfunction remain largely unknown. The purpose of this study was to elucidate molecular mediators that connect nano-TiO 2 exposure with impaired cardiac function. Specifically, we were interested in the role of microRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…We, and others, have identi ed that maternal exposures to ENM during gestation can initiate developmental onset of disease within the maturing fetus. In laboratory studies, young and adult offspring have been reported to exhibit coronary dysfunction [40,41,42,43,44,45], vascular perturbations [27,45], reproductive consequences [46,47,48,49,50], and neurodevelopmental delays [51,52] after maternal inhalation of engineered nanomaterials during pregnancy. Therefore, particle deposition, and likely particle accumulation and retention, impact offspring health after birth and into adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…We, and others, have identi ed that maternal exposures to ENM during gestation can initiate developmental onset of disease within the maturing fetus. In laboratory studies, young and adult offspring have been reported to exhibit coronary dysfunction [40,41,42,43,44,45], vascular perturbations [27,45], reproductive consequences [46,47,48,49,50], and neurodevelopmental delays [51,52] after maternal inhalation of engineered nanomaterials during pregnancy. Therefore, particle deposition, and likely particle accumulation and retention, impact offspring health after birth and into adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…[55] Mitochondrial dysfunction caused by nano-TiO 2 contributes to cardiac dysfunction, partially mediated by overexpression of microRNA-378a. [56] Residing within the first intron of the PGC-1b, [56] microRNA-378a acts as a negative regulator of mitochondrial oxidative metabolism and mitochondrial biogenesis pathways. [57] The expression of MiRNA-378a increased after inhalation of nano-TiO 2 , and the MiRNA-378a knock-out showed a cardioprotective effect.…”
Section: Circulatory and Cardiovascular Systemmentioning
confidence: 99%
“…Thus, fetal mice (prenatally exposed to ≈10 mg m −3 of nano-TiO 2 [54,59] ) showed negligible change in cardiac output. In adult isogenic [59] and heterozygous mice, [56] nano-TiO 2 caused more significant increased cardiac output, whereas in adult wild type and MiRNA-378a knockout mice the cardiac output notably decreased in response to nano-TiO 2 inhalation ( Figure 1).…”
Section: Circulatory and Cardiovascular Systemmentioning
confidence: 99%
“…We, and others, have identi ed that maternal exposures to metallic and carbonaceous ENM during gestation can initiate developmental onset of disease within the maturing fetus. In laboratory studies, young and adult offspring have been reported to exhibit coronary dysfunction [33,34,35,36,37,38], vascular perturbations [38,39], negative reproductive health outcomes [40,41,42], and neurological outcomes [43,44,45] after maternal inhalation of engineered nanomaterials during pregnancy. It is also plausible that these ndings represent a snapshot of time, wherein the particles reach the fetal tissues within 24 hours of exposure but are removed from the fetal circulation prior to birth.…”
Section: Discussionmentioning
confidence: 99%